TARHANA OTUNUN ( ECHİNOPHORA TENUİFOLİA SUBSP. SİBTHORPİANA) ŞAVAK TULUM PEYNİRİNİN KALİTESİ ÜZERİNE ETKİSİNİN İNCELENMESİ - DENİZ, AYBİKE REYYAN (Fırat Üniveristesi, 2024)
TARHANA OTUNUN (Echinophora tenuifolia subsp. sibthorpiana) ŞAVAK TULUM PEYNİRİNİN KALİTESİ ÜZERİNDEKİ ETKİSİNİN İNCELENMESİ Bu araştırmada, tarhana otunun (Echinophora tenuifolia subsp. sibthorpiana) Şavak tulum peynirinin kalitesi üzerindeki etkisi incelendi. Bu amaçla, biri kontrol, diğeri ise tarhana otu içeren iki grup tulum peyniri yapıldı. Otlu peynir üretiminde, pıhtı oluşturulduktan sonra süzülme aşamasında süzek bezine bir sıra pıhtı, bir sıra da peynir üretiminde kullanılan sütün %2'si oranında salamura edilmiş taze tarhana otu eklendi ve teleme süzüldü. Teleme, 100 gramlık plastik bidonlara konuldu ve +4°C'de 4 ay muhafaza edildi. Muhafazanın başlangıç günü (0. gün), 30.,60.,90. ve 120. günlerinde mikrobiyal (Toplam mezofilik aerob bakteri, toplam psikrotrof aerob bakteri, koliform bakteri, Enterobacteriaceae, lipolitik, proteolitik, Lactobacillus-Leuconostoc-Pediococcus (LLP), laktik streptokoklar, maya ve küf), kimyasal (yağ asitleri, retinol, D2, D3, ?-tokoferol, stigmatokoferol, K2, K3 vitaminleri, kolesterol, kuru madde, yağ, tuz, asitlik tayini ve pH değeri) kalite bakımından incelendi. Duyusal analizler ise muhafazanın 45. 60., 90. ve 120. günlerinde yapıldı. İstatistiksel olarak, gruplar arası ve grup içi günler arasındaki farklılığın önem derecesi araştırılmıştır. Mikroorganizma sayıları log10 kob/g olarak toplam mezofilik aerob bakteri sayısı kontrol peynirinde 7.02-8.20, otlu peynirde 7.55-.8.91, toplam psikrotrof aerob bakteri sayısı kontrol grubunda 6.20-6.79, otlu grupta 6.10-7.34, LLP bakteri sayısı kontrol peynirinde 5.76-8.41, otlu peynirde ise 6.87-8.00, laktik streptokok bakteri sayısı kontrol peynirinde 7.37-8.44, otlu peynirde ise 7.65-8.66, lipolitik bakteri sayısı kontrol peynirinde 7.76-8.32, otlu peynirde ise 7.90-8.88, koliform bakteri sayısı kontrol peynirinde 4.70-5.38, otlu peynirde ise 4.80-5.74, enterobacteriaceae sayısı kontrol peynirinde 6.21-6.67 otlu peynirde ise 6.02-7.16, maya ve küf bakteri sayısı kontrol peynirinde 5.07–6.25, otlu peynirde ise 5.21–6.01, proteolitik bakteri sayısı kontrol peynirinde 4.86–7.23, otlu peynirde ise 4.65–7.27 arasında saptandı. Kimyasal özellikler bakımından pH değerleri kontrol peynirinde 5.72–6.39, otlu peynirde 5.82–6.51 aralığında; asitlik ise kontrolde 1.02–2.03, otlu grupta 1.14–1.96, kuru madde oranı kontrol grubunda 53.22–54.96, otlu grupta 52.17–53.66, yağ kontrolde 47.15-48.15, otlu grupta 44.15-45.17, tuz oranları kontrolde 8.61–9.16, otlu peynirde 8.22–9.37 arasında saptandı. Toplam doymuş yağ asitleri (incelenen toplam yağ asitlerindeki % oranı ) değerleri kontrol grubunda 48.71–68.61, otlu grupta 48.62–68.75, toplam doymamış yağ asitleri (incelenen toplam yağ asitlerindeki % oranı ) değerleri, kontrol grubunda 27.12–50.11, otlu grupta ise 26.91–47.92, toplam tekli doymamış yağ asitleri (incelenen toplam doymamış yağ asitlerindeki % oranı ) değerleri, kontrol grubunda 28.27–48.11, otlu grupta ise 27.91–47.92, toplam çoklu doymamış yağ asitleri (incelenen toplam doymamış yağ asitlerindeki % oranı ) değerleri, kontrol grubunda 2.73–3.32, otlu grupta ise 3.25–3.66 arasında saptandı. Vitamin değerleri ?g/g olarak; K1 vitamini kontrol grubunda 1.22–3.64, otlu grupta 0.80–2.97, K2 vitamini kontrol grubunda 27.73–39.62, otlu grupta 21.71–27.46, D2 vitamini kontrol grubunda 1.20–1.80, otlu grupta 0.69–1.53, D3 vitamini kontrol grubunda 0.62–1.73, otlu grupta 0.53–1.13, stigmatokoferol değeri kontrol grubunda 9.20–18.99, otlu grupta 6.31–17.93, ?-tokoferol değeri kontrol grubunda 1.63–5.35 , otlu grupta 1.33–3.24, retinol miktarı kontrol grubunda 0.71–0.82, otlu grupta 0.77–0.98, kolesterol düzeyi ise kontrol grubunda 352.69–500.58, otlu grupta 245.97–453.73 arasında tespit edildi. Renk analizlerinde L* değeri (açıklık) kontrol grubunda 7.64–7.79, otlu grupta 7.67–7.77, a* değeri (kırmızılık) kontrol peynirinde 0.93–1.31,otlu grupta 0.76–1.22, b* değeri (sarılık) ise kontrol grubunda 1.73–2.33, otlu peynirde 1.81–2.09 arasında saptandı. Duyusal analizler sonucunda; kesit ve görünüş puanları kontrol peynirinde 85.71–88.00, otlu grupta 78.00–84.00, kıvam puanları kontrol grubunda 88.00–90.00, otlu grupta 80.00–90.00, koku puanları kontrol grubunda 80.00–90.00, otlu grupta 76.00–83.00, lezzet puanı ise kontrol grubunda 80.00–90.00, otlu grupta 78.00–82.85 arasında belirlendi. Sonuç olarak, buzdolabında 120 gün kalitesini koruyabilen duyusal nitelikleri tulum peynirinden farklı, fonksiyonel tarhana otlu Şavak tulum peynirinin üretilebileceği vurgulanabilir. Anahtar Kelimeler: Tarhana otu, Echinophora tenuifolia, Şavak otlu tulum peyniri

INVESTIGATION OF THE EFFECT OF TARHANA HERB (Echinophora tenuifolia subsp. sibthorpiana) ON THE QUALITY OF ŞAVAK TULUM CHEESE In this study, the effect of tarhana herb ((Echinophora tenuifolia subsp. sibthorpiana)) on the quality of Şavak tulum cheese was investigated. For this purpose, two groups of tulum cheese were produced: one as the control group and the other as herby tulum cheese containing tarhana herb. In the production of the herby cheese, after the curd was formed, during the draining stage, a layer of curd was placed in the cheesecloth, followed by a layer of fresh tarhana herb brined at 2% of the milk used in cheese production, and the curd was drained. The curd was then placed in 100-gram plastic jars and stored at +4°C for 4 months. Microbiological (total mesophilic aerobic bacteria, total psychrotrophic aerobic bacteria, coliform bacteria, Enterobacteriaceae, lipolytic bacteria, proteolytic bacteria, Lactobacillus–Leuconostoc–Pediococcus (LLP), lactic streptococci, yeast and mold) and chemical (fatty acids, vitamins retinol, D2, D3, ?-tokoferol, stigmatokoferol, K2, K3, cholesterol, dry matter, fat, salt, acidity, and pH) quality parameters were examined on the first day of storage (day 0), and on the 30th, 60th, 90th, and 120th days. Sensory analyses were carried out starting from the 45th day of storage and, along with other analyses, were conducted on the 60th, 90th, and 120th days. Statistical analysis was performed to determine the significance of differences between groups and within days of each group. Microorganism counts (log10 cfu/g) were determined as follows: total mesophilic aerobic bacteria counts ranged from 7.02 - 8.20 in control cheese and from 7.55 -8.91 in herby cheese; total psychrotrophic aerobic bacteria counts ranged from 6.20 -6.79 in the control group and from 6.10 -7.34 in the herby group; LLP bacteria counts ranged from 5.76 - 8.41 in control cheese and from 6.87 -8.00 in herby cheese; lactic streptococci counts ranged from 7.37- 8.44 in control cheese and from 7.65 - 8.66 in herby cheese; lipolytic bacteria counts ranged from 7.76 - 8.32 in control cheese and from 7.90- 8.88 in herby cheese; coliform bacteria counts ranged from 4.70 - 5.38 in control cheese and from 4.80 - 5.74 in herby cheese; Enterobacteriaceae counts ranged from 6.21- 6.67in control cheese and from 6.02 -7.16 in herby cheese; yeast and mold counts ranged from 5.07 - 6.25 in control cheese and from 5.21 - 6.01 in herby cheese; proteolytic bacteria counts ranged from 4.86 - 7.23 in control cheese and from 4.65 -7.27 in herby cheese. Regarding chemical properties, pH values ranged from 5.72 - 6.39 in control cheese and from 5.82 - 6.51 in herby cheese; acidity ranged from 1.02- 2.03 in control cheese and from 1.14 - 1.96 in herby cheese; dry matter content ranged from 53.22% - 54.96% in the control group and from 52.17% - 53.66% in the herby group; fat content ranged from 47.15% -48.15% in control cheese and from 44.15% - 45.17% in herby cheese; salt content ranged from 8.61% - 9.16% in control cheese and from 8.22% -9.37% in herby cheese. Fatty acid composition, expressed as the percentage of each fatty acid examined, was as follows: total saturated fatty acids ranged from 48.71% -68.61% in the control group and from 48.62% - 68.75% in herby cheese; total unsaturated fatty acids ranged from 27.12% - 50.11% in the control group and from 26.91% - 47.92% in the herby group; total monounsaturated fatty acids (as a percentage of total unsaturated fatty acids) ranged from 28.27%- 48.11% in the control group and from 27.91% - 47.92% in the herby group; total polyunsaturated fatty acids (as a percentage of total unsaturated fatty acids) ranged from 2.73% -3.32% in the control group and from 3.25% - 3.66% in the herby group. Vitamin contents (µg/g) were determined as follows: vitamin K1 ranged from 1.22 - 3.64 in the control group and from 0.80 - 2.97 in the herby group; vitamin K2 ranged from 27.73- 39.62 in the control group and from 21.71 - 27.46 in the herby group; vitamin D2 ranged from 1.20 - 1.80 in the control group and from 0.69 - 1.53 in the herby group; vitamin D3 ranged from 0.62 -1.73 in the control group and from 0.53 - 1.13 in the herby group; stigmatocopherol ranged from 9.20 - 18.99 in the control group and from 6.31 -17.93 in the herby group; ?-tocopherol ranged from 1.63 - 5.35 in the control group and from 1.33- 3.24 in the herby group; retinol ranged from 0.71 - 0.82 in the control group and from 0.77 - 0.98 in the herby group; cholesterol ranged from 352.69 - 500.58 in the control group and from 245.97 - 453.73 in the herby group. In color analysis, L* values (lightness) ranged from 7.64 -7.79 in the control group and from 7.67- 7.77 in the herby group; a* values (redness) ranged from 0.93 - 1.31 in control cheese and from 0.76 - 1.22 in herby cheese; b* values (yellowness) ranged from 1.73 -2.33 in the control group and from 1.81 - 2.09 in herby cheese. Sensory analysis results showed that section and appearance scores ranged from 85.71 - 88.00 in control cheese and from 78.00 - 84.00 in the herby group; texture scores ranged from 88.00 - 90.00 in the control group and from 80.00 - 90.00 in the herby group; odor scores ranged from 80.00 -90.00 in the control group and from 76.00 - 83.00 in the herby group; taste scores ranged from 80.00 - 90.00 in the control group and from 78.00 -82.85 in the herby group. In conclusion, it can be emphasized that it is possible to produce a functional Şavak herby tulum cheese containing tarhana herb, with sensory properties that can be preserved for 120 days under refrigeration, differing from traditional tulum cheese. Keywords: Tarhana herb, Echinophora tenuifolia, Şavak herby tulum cheese
Using Yellow hyssop/ Tarhana ( Echinophora tenuifolia subsp. Sibthorpiana)in making tulum cheese
Keywords: Besin Hijyeni ve Teknolojisi